2010
DOI: 10.1177/0022466910369941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link Among Behavior Intervention Plans, Treatment Integrity, and Student Outcomes Under Natural Educational Conditions

Abstract: Several researchers have argued that the functional behavior assessment (FBA) and behavior intervention plan (BIP) mandates in the Individuals With Disabilities Education Act of 2004 have gone beyond the current research base. For instance, although BIPs have been shown to improve student outcomes when implemented with strict control and oversight by researchers, it is unclear whether these relationships hold true when implemented under real educational conditions. The purpose of this research was to conduct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 40 publications
(41 reference statements)
3
53
0
Order By: Relevance
“…The ultimate goal is for typical caregivers to apply PBS principles to resolve challenges on their own, thereby reducing dependence on outside professionals. The effectiveness of engaging caregivers has been demonstrated in work with families (Fettig and Barton 2014) and educators (Cook et al 2012), with studies indicating that typical caregivers can be engaged as partners in the assessment, be responsible for the implementation of the resulting function-based interventions, and produce improvements in child behavior.…”
Section: Collaborating With Typical Caregiversmentioning
confidence: 99%
“…The ultimate goal is for typical caregivers to apply PBS principles to resolve challenges on their own, thereby reducing dependence on outside professionals. The effectiveness of engaging caregivers has been demonstrated in work with families (Fettig and Barton 2014) and educators (Cook et al 2012), with studies indicating that typical caregivers can be engaged as partners in the assessment, be responsible for the implementation of the resulting function-based interventions, and produce improvements in child behavior.…”
Section: Collaborating With Typical Caregiversmentioning
confidence: 99%
“…In addition to minimizing Dean's disruptive and inappropriate classroom behaviors, the plan was implemented to encourage him to apply the skills he learned in counseling sessions to the classroom and engage in behaviors that could cultivate his academic success. Cook et al (2010) found that students are more likely to reduce their problematic behaviors when behavior intervention plans are implemented with integrity. Thus, multiple strategies were employed to ensure that the classroom behavior plan was implemented as intended.…”
Section: Goal 3: Behavioral and Cognitive Interventionsmentioning
confidence: 97%
“…Eames et al (2009) found that positive group leader behaviors, such as encouragement, predicted improved observed and parent-reported parenting, which resulted in increased child compliance and prosocial behaviors. Furthermore, skillful interactions with clients may contribute to decreased problem behaviors and increased appropriate behaviors, as well as positive behavior generalization in youths (Cook et al, 2012). Skillful implementation of a health-related parenting program has been associated with improved health outcomes for adolescents by improving adolescent compliance with treatment regimens (Ellis, Naar-King, Cinningham, Templin, & Frey, 2007).…”
Section: Adherence Dosage and Quality Assessmentmentioning
confidence: 99%